Laparoscopic repair of perforated peptic ulcers without omental patch versus conventional open surgery - Srivastava, Vaibhav; Singh, Gyanendra; Singh, Santosh K. (International Surgery Journal, 2018)
Background: Perforation of peptic ulcer usually presents as an acute abdomen. Nearly one third of the patients have no history of the disease. Laparoscopic surgery, a minimally invasive technique, has recently begun to be used on perforated peptic ulcers effectively and frequently. This study aimed to evaluate the efficacy, safety and outcome of laparoscopic surgery without omental patch for perforated ulcers in comparison with conventional open surgery. Methods: All patients diagnosed clinically with perforated peptic ulcers presenting within 24 hours of symptoms and undergoing surgery under a single surgeon during 1-year interval were included in this study and randomly assigned to laparoscopic and open repair group. Patients who had to be converted from laparoscopic surgery to open surgery, were excluded. Results: A total of 69 patients were included in this study. Number of doses of analgesics required in laparoscopic group was 9.48 ± 1.82, while those required in conventional open group was 18.16±2.24. In laparoscopic duodenal perforation repair group, duration of hospital stay (in days) was 8.42±1.44 as compared to 12.08±4.82 in open repair group. Laparoscopic group had significantly fewer post-operative complications but had longer mean operative time (101.90 minutes compared to 60.32 minutes in open repair group). Conclusions: Laparoscopic closure of perforated duodenal ulcer is a simple and safe procedure in experienced hands. It maintains the benefits of the minimally invasive approach. It is associated with longer operating time, less postoperative pain, less post-operative complications, a shorter postoperative hospital stay, and earlier returns to normal daily activities.